Recycle Pakaian Bekas Dan Limbah Kain Menjadi Pelengkap Busana dan Lenan Rumah Tangga - Mien Zyahratil Umami; Romadhona Chusna Tsani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Fabric waste was one type of inorganic waste that was not easily decomposed so it cannot be composted. If destroyed by burning, it will produce smoke and toxic gases that harm the environment. Recycle is an effort made in reducing used clothing waste. The process carried out is to convert used clothing and fabric waste into new products that have use value and selling value. The aim of the study was to convert used clothing and fabric waste into complementary clothing and household linen. The method used is a qualitative method. The recycling process of used clothes is carried out through 3 stages, the orientation stage, the reduction stage, and the selection process. The first process was to create a design, making patterns, cutting used clothes and fabric waste and sewing. The products produced from the research on recycling used clothing and cloth waste are in the form of complementary clothing products and household waste such as totte bags, tissue holders, seat cushion covers and bandanas. Based on the research on recycling used clothes and cloth waste to complement clothing and household waste, researchers can provide several suggestions, including choosing used clothes with various motifs, fabrics that have sharp colors will add innovation in the manufacture of new products. It was recommended to recycle used clothes using a zero waste technique, this technique was intended to minimize new fabric waste, the rest of the recycled used clothes.